Acute acquired comitant esotropia: Current understanding of its etiological classification and treatment strategies - Noriko Nishikawa; Miho Sato (Taiwan Journal of Ophthalmology)
Acute acquired comitant esotropia (AACE) is characterized by acute onset of esotropia without limitation of eye movements in children and adults. AACE has been considered relatively rare, and most previous reports were small case series. However, recently, there has been great interest in this disease because of the rapid increase in the number of cases speculated to be related to the use of digital devices. In a growing number of studies, disputes remain regarding its etiology, clinical features, management, and classification. Herein, we review the literature on the history, clinical features, possible etiologic classifications, and treatment strategies for AACE to provide a comprehensive and updated understanding of the disease.